The Modern kitchen objects that changed the way we cook, eat and live - Hayward, Tim; Hogan, Sarah (London Quadrille, 2017)
The kitchen is the heart of the home – it's where we spend leisure time as a family, where we feed ourselves and where we entertain our friends. The average western family spends more money on the kitchen than they do on a car or a vacation. We fill our kitchens with objects and tools that reflect our needs, tastes and desires. There is nowhere else in daily domestic life where design impinges quite as much as in the kitchen. Every item in the kitchen has its own story. Through 100 familiar objects, The Modern Kitchen maps the progress and development of this functional yet also wildly aspirational space. Why do the Le Creuset casserole dish and the wooden salad bowl exert such a cultural hold over us? Has the accumulation of electrical appliances led us to cook and eat differently? As well as studying the individual objects that have had such a huge impact on the way we live now, The Modern Kitchen examines kitchen design, economics, and gender politics through a series of essays. Embodying notions about class, gender, wealth, and health, the home kitchen and its layout, set-up, and contents, remains a neat illustration of our beliefs, tastes, aesthetics, and aspirations – the portrait of our domestic lives.--Provided by publisher.
Keywords: Kitchens; Kitchen utensils